2021
DOI: 10.1186/s10033-020-00505-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Reduction of Pressure Fluctuation for a Double-Suction Centrifugal Pump

Abstract: Double-suction centrifugal pumps have been applied extensively in many areas, and the significance of pressure fluctuations inside these pumps with large power is becoming increasingly important. In this study, a double-suction centrifugal pump with a high-demand for vibration and noise was redesigned by increasing the flow uniformity at the impeller discharge, implemented by combinations of more than two parameters. First, increasing the number of the impeller blades was intended to enhance the bounding effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Centrifugal pumps are an important class of rotating machinery that has garnered significant attention over recent years [1][2][3][4]. The effectiveness of the sealing structure is crucial for ensuring the safety, reliability and economy of centrifugal pumps.…”
Section: Introductionmentioning
confidence: 99%
“…Centrifugal pumps are an important class of rotating machinery that has garnered significant attention over recent years [1][2][3][4]. The effectiveness of the sealing structure is crucial for ensuring the safety, reliability and economy of centrifugal pumps.…”
Section: Introductionmentioning
confidence: 99%
“…The centrifugal force created by the rotating impeller moves the liquid out along the impeller blades, increasing kinetic energy. After the fluid leaves the impellers, it exits the pump through a spiral casing of increasing crosssectional area (the convolute), at which time, the kinetic energy is converted to work energy, i.e., pressure head [5]. The integral two parts of many pumping systems are the pump and pipeline [4,6,7] which are connected by the fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Their numerical work revealed that the backflow at the volute tongue is the chief factor of the caused instability, which grows with the decrease of the flow rate. Li et al (2021) redesigned a double-suction centrifugal pump to reduce the reported noise and vibration. This intention which was done by adding to impeller blades as well as increasing the radial gap between the impeller and volute, resulted in about 6% of decrease in pressure fluctuation amplitudes.…”
Section: Introductionmentioning
confidence: 99%